Education and Message Framing Increase Willingness to Undergo Research Lumbar Puncture: A Randomized Controlled Trial - Witbracht, Megan G.; Bernstein, Olivia M.; Lin, Vanessa; Salazar, Christian R.; Sajjadi, S. Ahmad; Hoang, Dan; Cox, Chelsea G.; Gillen, Daniel L.; Grill, Joshua D. (Frontiers in Medicine, 2020)
Reluctance to undergo lumbar puncture (LP) is a barrier to neurological disease biomarker research. We assessed whether an educational intervention increased willingness to consider research LP and whether message framing modified intervention effectiveness. We randomly assigned 851 recruitment registry enrollees who had previously indicated they were unwilling to be contacted about studies requiring LP to gain or loss framed video educational interventions describing the procedure and the probability of experiencing adverse events. The gain framed intervention emphasized the proportion of individuals free of adverse events; the loss frame emphasized the proportion experiencing adverse events. The primary outcome for the study was the participant’s post-intervention agreement to be contacted about studies requiring LP. Participants were mean (SD) age 60.1 years (15.7), 69% female, and mostly college educated and white. Among the 699 participants who completed the study, 42% changed their response to agree to be contacted about studies requiring LP. We estimated that participants randomized to the gain framed intervention had 67% higher odds of changing their response compared to those randomized to the loss frame (Odds Ratio = 1.67; 95% CI: 1.24, 2.26; p < 0.001). A classification and regression tree model identified participants’ pre-intervention willingness as the strongest predictor of changing response. Education, in particular education that emphasizes the probability of not experiencing adverse events, may be an effective tool to increase participation rates in research requiring LP.